1998
DOI: 10.1046/j.1365-294x.1998.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wild‐type and genetically modified Pseudomonas fluorescens on soil enzyme activities and microbial population structure in the rhizosphere of pea

Abstract: The aim of this study was to determine the impact of wild‐type along with functionally and nonfunctionally modified Pseudomonas fluorescens strains in the rhizosphere. The wild‐type F113 strain carried a gene encoding the production of the antibiotic 2,4‐diacetylphloroglucinol (DAPG) useful in plant disease control, and was marked with a lacZY gene cassette. The first modified strain was a functional modification of strain F113 with repressed production of DAPG, creating the DAPG‐negative strain F113 G22. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 37 publications
(47 reference statements)
1
30
0
Order By: Relevance
“…Pseudomonas spp. can colonize the roots of a wide range of plants (Simons et al, 1996;Naseby & Lynch, 1998;Villacieros et al, 2003), being one of the best root colonizers, and are used as a model in root-colonization studies (Bloemberg et al, 2000; Chin-a-Woeng et al, 2000). The rhizosphere is a complex environment that supports a large and metabolically active microbial population, several orders of magnitude higher than the non-rhizospheric soil.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas spp. can colonize the roots of a wide range of plants (Simons et al, 1996;Naseby & Lynch, 1998;Villacieros et al, 2003), being one of the best root colonizers, and are used as a model in root-colonization studies (Bloemberg et al, 2000; Chin-a-Woeng et al, 2000). The rhizosphere is a complex environment that supports a large and metabolically active microbial population, several orders of magnitude higher than the non-rhizospheric soil.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect evidence of perturbations caused by bacterial inoculants on the indigenous bacterial community of the rhizosphere has been obtained by studying community-level catabolic profiles on BIOLOG plates, microbial enzymatic activities, profiles of fatty acid methyl esters extracted from the rhizosphere, and/or the distribution of r/K strategists on plates (10,11,34,37,46). The impact of biocontrol pseudomonads on the diversity of the bacterial community has been investigated at the level of the genus and/or species (26,37), and it can be expected that this type of work will benefit from current developments in molecular, culture-independent approaches (25,38).…”
mentioning
confidence: 99%
“…The persistence of rhizobia bearing genetic modifications has been related to many factors mainly regarding soil type, presence of host legume and competing co-specific strains (Hagen et al, 1997). In relation to lactose, microcosm soil trials performed in pea rhizospheres with Pseudomonas fluorescens carrying lacZY, during a 21 days incubation, showed that the substrate could enhance the GMM recovery by 0.3 of a log unit (Naseby and Lynch, 1998).…”
Section: Discussionmentioning
confidence: 99%